Effect of Contact Pressure on the Resistance Contact Value and Temperature Changes in Copper Busbar Connection - Risdiyanto, Agus; Rachman, Noviadi Arief; Arifin, Maulana (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2012)
This paper discussed the influence of tightness or contacts pressure on copper busbar joints to determine changes in the value of the initial contact resistance and the maximum temperature at the joint due to high current load. The test sample was copper busbar 3 x 30 mm with configuration of bolted overlapping joint. Increasing contact pressure at the joint was measured to find out its effect on the value of contact resistance. The applied pressure was 6 to 36 MPa. Procedure of contact resistance measurement refer to the ASTM B539 standard using four-wire method. The sample subsequently loaded with the current of 350 A for 60 minutes and the maximum temperature at the joint was measured. The result showed that increasing contact pressure at the busbar joint will reduce the contact resistance and maximum temperature. The increase of contact pressure from 6 to 30 MPa causes decreasing contact resistance from 16 Î¼Î© to 11 Î¼Î©. Further increasing of contact pressure more than 30 MPa did not affect the contact resistance significantly. The lowest temperatur of busbar joint of 54Â°C was reached at a contact pressure of 36 Mpa.